Polinomios de 3º de ESO VI

Ejercicio 6º resuelto

Multiplicar:

1(x4 − 2x² + 2) · (x² − 2x + 3) =

= x 6 − 2x5 + 3x4 − 2x4 + 4x³ − 6x² + 2x² − 4x + 6=

= x 6 − 2x5 − 2x4 + 3x4 + 4x³ + 2x² − 6x² − 4x + 6 =

= x 6 −2x5 + x4 + 4x³− 4x² − 4x + 6

2 (3x² − 5x) · (2x³ + 4x² − x + 2) =

= 6x5 + 12x4 − 3x³ + 6x² − 10x4 − 20x³ + 5x² − 10x =

= 6x5 + 12x4 − 10x4 − 3x³ − 20x³ + 6x² + 5x² − 10x =

= 6x5 + 2x4 − 23x³ + 11x² − 10x

3(2x² − 5x + 6) · (3x4 − 5 x³ − 6 x² + 4x − 3) =

= 6x6 − 10x5 − 12x4 + 8x³ − 6x² −

− 15x5 + 25x4 + 30x³ − 20x² + 15x +

+18x4 − 30x³ − 36x² + 24x − 18 =

= 6x6 − 10x5 − 15x5 − 12x4 + 25x4 + 18x4 +

+8x³ − 30x³ + 30x³ − 6x²− 20x² − 36x² + 15x + 24x − 18 =

= 6x6 − 25x5 + 31x4 + 8x³ − 62x² + 39x − 18